Evaluation of a Reading Lesson - Papadaki, Aggeliki; Karagianni, Eleni (Eximia, 2023)
The aim of the article is to evaluate a particular reading lesson based on certain criteria. It is composed of four parts. In the first part, there is a brief description of the stages of the reading lesson. In the second one, there is a presentation of the actual criteria and in the third part, an evaluation of the reading lesson as a whole and its reading activities, based on the above criteria. Finally, in the fourth part, there are some suggestions/ modifications of specific activities, so as to suit learners’ needs.